Nanotoxicology : materials, methodologies, and assessments - Duran, Nelson,lcco; Guterres, Silvia; Alves, Oswaldo L. (Nanomedicine and nanotoxicology.)
This book takes a systematic approach to nanotoxicology and the developing risk factors associated with nanosized particles during manufacture and use of nanotechnology. Beginning with a detailed introduction to engineered nanostructures, the first part of the book presents concepts and definitions of nanomaterials from quantum dots to graphene to fullerenes, with detailed discussion of functionalization, stability, and medical and biological applications. The second part critically examines methodologies used to assess cytotoxicity and genotoxicity.--